CHRONIC RECURRENT APHTHOSIS STOMATITIS - Radjabov Alisher Islomovich; Ziyaeva Feruza Ravshanovna (Scholar Express Journal, 2023)
Pathology of the verbal mucosa has a special place among dental diseases because its occurrence and clinical manifestations are regularly related to the influence of numerous local and general causes. The distinctive features of aphthous stomatitis appearance in women of fertile age taking methotrexate were the accessibility of a pronounced painful symptom, a sluggish slowly progressing permanent course, prolonged period of recovery processes extension, and agonizing quality of regional lymph hubs
Keywords: aphtha; relapse; stomatitis; ulcer